KEBIJAKAN PERSEDIAAN (s, Q) DAN (R, S) PADA MODEL PERSEDIAAN DETERMINISTIK DAN STOKASTIK - , HARIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research develops a mathematical model for the optimalization of system inventory policy (s, Q) and (R, S) in order to minimize the total cost of inventory. This is done by using a model of inventory that is stochastic and deterministic on inventory policy (s, Q) and (R, S). Stochastic inventory model is divided into two distinct policies is policy system (s, Q) which reviewed continuously and policy system (R, S) which reviewed periodically. Each system is the policy used to determine the total cost of inventory of what was in the review. Policy (s, Q) and (R, S) will resolve inventory issues in the review continuously and periodically.